Proceedings of the 24th International ACM SIGACCESS Conference on Computers and Accessibility 2022
DOI: 10.1145/3517428.3550401
|View full text |Cite
|
Sign up to set email alerts
|

PigScape: An embodied video game for cognitive peer-training of impulse and behavior control in children with ADHD

Abstract: This paper describes a therapeutic full-body controlled video game for children with attention deficit / hyperactivity disorder (ADHD).The game supports a co-located gameplay with a depth-sensing camera and a large media screen. Children play the game in pairs for improved impulse and behavior control, self-regulation, peer-communication, and emotion regulation. The gaming was implemented as a part of a neuropsychological group intervention for children with confirmed deficits in attention or diagnosed ADHD. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Hence, we could assume that our three difficulty settings worked well in aligning the exergame's challenge to the individual abilities. Our research findings were in line with Anguera's positive attitude towards the adaptive staircase difficulty, which was lacking in many studies on game design [8,41,64,72]. Our findings suggested it is a potential direction that assessing the participant's performance and setting dynamic increasing difficulty in future research.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Hence, we could assume that our three difficulty settings worked well in aligning the exergame's challenge to the individual abilities. Our research findings were in line with Anguera's positive attitude towards the adaptive staircase difficulty, which was lacking in many studies on game design [8,41,64,72]. Our findings suggested it is a potential direction that assessing the participant's performance and setting dynamic increasing difficulty in future research.…”
supporting
confidence: 85%
“…Motivation and satisfaction are key factors in determining the effectiveness of gamified training [41]. When participants experience both interest and challenge in a game, they enter the flow state, leading to increased engagement and greater time and effort invested [25].…”
Section: Dg2: Motivation In Encouraging Active Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…The multiplayer game 'PigScape' supports co-located gameplay, meaning that children play in pairs. This setup aims to create a learning environment in which children can support each other and enhance their social interactions and communication skills [63]. In particular, 'ADDventurous Rhythmical Planet' offers the option to play alone or in collaboration with others, employing a multi-user mode that fosters teamwork and communication.…”
Section: Social Skillsmentioning
confidence: 99%
“…17% (2/12) of the studies aimed at enhancing children's emotion regulation [39,56], viewed as integrating cognitive flexibility and inhibitory control. Another 17% (2/12) of the studies focused on improving Hyperactivity-Impulsivity symptoms with counter-intuitive game rules designed to stimulate impulsive responses, requiring players to inhibit these responses to succeed, and the game's difficulty can be adjusted based on the child's progress [57,63]. The remaining 3 studies reported synthesizing improvements in executive function through multiple mini-games [41,48,58].…”
Section: Executive Functionsmentioning
confidence: 99%